2016
DOI: 10.1016/j.landusepol.2015.10.026
|View full text |Cite
|
Sign up to set email alerts
|

Trends in private land conservation: Increasing complexity, shifting conservation purposes and allowable private land uses

Abstract: The terrain of private-land conservation dealmaking is shifting. As the number of acres of private land protected for conservation increases, our understanding of what it means for a property to be "conserved" is shifting. We examined 269 conservation easements and conducted 73 interviews with land conservation organizations to investigate changes in private-land conservation in the United States. We hypothesized that since 2000, conservation easements have become more complex but less restrictive. Our analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
23
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 17 publications
2
23
0
1
Order By: Relevance
“…While the CLTIP is different from conservation easements in several respects, such as the duration of the commitment and the extent to which land uses may be allowed (Owley and Rissman 2016), both types of conservation tools are voluntary, lead to property tax advantages, and largely aim to keep the targeted land in its current state. Farmer et al (2011) found that place attachment was the most important factor for private landowners to place a conservation easement on their land.…”
Section: Discussionmentioning
confidence: 99%
“…While the CLTIP is different from conservation easements in several respects, such as the duration of the commitment and the extent to which land uses may be allowed (Owley and Rissman 2016), both types of conservation tools are voluntary, lead to property tax advantages, and largely aim to keep the targeted land in its current state. Farmer et al (2011) found that place attachment was the most important factor for private landowners to place a conservation easement on their land.…”
Section: Discussionmentioning
confidence: 99%
“…Throughout the state, conservation measures (such as zoning regulations, conservation purchases, conservation easements, etc.) have been designed to protect the health and function of coastal ecosystems, and to preserve the scenic, and recreational value of these lands (Endicott, 1993;Newburn, Reed, Berck, & Merenlender, 2005;Yonavjak & Gartner, 2011;Wilson et al, 2015;Owley & Rissman, 2016). However, a common challenge to policy makers, and resource managers is understanding the effectiveness of such policies.…”
Section: Discussionmentioning
confidence: 99%
“…Incentive-based programs can suffer from problems in cost, efficacy, and enforcement, yet have advantages over more traditional practices (Griesedieck 2007) and both economic and social incentives can be used to promote many conservation programs. Easement and land purchases by land trusts can prevent development and raise community awareness for conservation (Milder and Clark 2011;Owley and Rissman 2016). But political and financial elements can make land trust operations complex.…”
Section: Discussion Conclusion and Recommendationsmentioning
confidence: 99%